Respon Emosional Orang Tua Dalam Merawat Anak Dengan Kanker Dalam Kondisi Perawatan Palliatif : Respon Emosional Orang Tua Dalam Merawat Anak Dengan Kanker Dalam Kondisi Perawatan Palliatif - Rina Mariyana; Allenidekania; Nani Nurhaeni (NERS Jurnal Keperawatan, 2018)
Cancer is one of the main causes of morbidity and mortality in the world. In caring for children with cancer, parents experienced many changes from this disease where parents feel giving up, feel emotional, and lack of communication between parents and the palliative team can influence the plan for palliative care in children. This study aims to explore the parents’ emotional response in caring for children with cancer under palliative care condition. The study was conducted at Jakarta, Bogor, and Bekasi. The research applied descriptive qualitative phenomenology design. Parents caring for children with cancer under palliative care were in-depth interviewed with open-ended questions. Data were then analyzed using the Colaizzi method. This study produced a theme. Anger, effort to distract their anger, exspression the anger, powerlessness. This study shows that during palliative care, parents experience a variety of emotional responses that they cannot control. Therefore, nurses are very important to provide an assessment and facilitate the fulfillment of needs that involve family members and religious experts to control the emotional response caused by the mother.